Strategi Meningkatkan Produktivitas Kerja: Kesejahteraan Karyawan Pengalaman Kerja dan Kinerja Sistem Informasi dalam Perspektif Kesehatan dan Keselamatan Kerja - Nurcahyo, Muhammad; Sutianingsih, Sutianingsih (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2024)
The objective of this study is to analyze the effects of various factors on the work productivity of employees of a motorcycle repair shop in Pacitan Regency. It was conducted quantitatively and involved sending out questionnaires to 30 of the shop's employees. The study was conducted using the Path Analysis and Descriptive Analysis techniques. The investigation results revealed that only the workers' safety and health conditions positively affected their productivity. They also stated that the work experience and occupational health did not affect the systems used by the shop. The study revealed that the direct and indirect effects of the different factors on the work performance of the employees were stronger than those of the information system. The information system could not mediate the effects of employee productivity and safety